Foucault and Rancière: learning and apprehending in dissent - Alvim, Mariana Freitas (2019)
In the book Diálogos e Dissidências: M. Foucault and J. Rancière, the authors present a synthesis of the theoretical paths and main concepts of these thinkers, essential in contemporary political philosophy. Agreements and particularities in their work are detailed, especially with regard to the possibilities of emancipation of individuals in the face of power.